Investigation of process parameter variation in the memristor based resistive random access memory (RRAM): Effect of device size variations. (July 2015) - Dongale, T.D.; Patil, K.P.; Mullani, S.B.; More, K.V.; Delekar, S.D.; Patil, P.S.; Gaikwad, P.K.; Kamat, R.K.
Abstract: The purpose of this work is to investigate the effect of device size and frequency on memristor based Resistive Random Access Memory (RRAM). The objects of investigation are effect on memory window, Low Resistance State (LRS) and High Resistance State (HRS) with memristor device size varied from 5 nm to 50 nm. Moreover, effect of device size variation on lifetime ( τ ) reliability of memristor device has also been explored. The results evidences that, memristor possess higher memory window and lifetime ( τ ) in the lower device size with lower frequencies. This subsequently consequences into lower data losses in the overall memory architecture having memristors as the basic building block. Authors have analysed effective variation in LRS and HRS by accomplishing Monte-Carlo simulation. The results of Monte-Carlo simulation suggests the LRS to follow Weibull distribution whereas HRS to go along with Gaussian distribution for less read and write errors.